2021
DOI: 10.3390/mps4030060
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Randomized Controlled Trial on the Effects of 12 Months of Combined Exercise Training during Hemodialysis in Patients with Chronic Kidney Disease—Study Protocol of the Dialysis Training Therapy (DiaTT) Trial

Abstract: Patients with chronic kidney disease (CKD) on hemodialysis (HD) experience treatment-related immobility and physical deconditioning, which is responsible for an increased risk of frailty and a high burden of multi-morbidity. Exercise has been shown to counteract this vicious cycle; however, its effectiveness has only been investigated in small cohorts. Therefore, the objective of the Dialysis Training Therapy (DiaTT) trial will be to assess the effects of a 12-month intradialytic exercise program on physical f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
(68 reference statements)
0
3
0
1
Order By: Relevance
“…Although some have suggested that dialysis patients should be routinely evaluated for frailty, 18 the utility of this approach is uncertain given the lack of proven interventions. Candidate therapies, such as exercise training, 19 androgen supplementation, 20 carnitine administration, 21 and perhaps other forms of nutritional support. 22 The high prevalence of frailty, the high associated costs, 23 and the excess risk of associated adverse outcomes indicate the need for clinical trials to identify effective treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Although some have suggested that dialysis patients should be routinely evaluated for frailty, 18 the utility of this approach is uncertain given the lack of proven interventions. Candidate therapies, such as exercise training, 19 androgen supplementation, 20 carnitine administration, 21 and perhaps other forms of nutritional support. 22 The high prevalence of frailty, the high associated costs, 23 and the excess risk of associated adverse outcomes indicate the need for clinical trials to identify effective treatments.…”
Section: Discussionmentioning
confidence: 99%
“…The association between frailty status and multiple adverse outcomes suggests that exercise-based interventions to improve physical function and mobility may have farreaching benefits in older adults with kidney disease [77]. Further studies, especially translational trials, are needed to characterise the relationship between kidney disease and frailty even better, and they are most important to identify opportunities to intervene.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in population studies higher moderate-vigorous physical activity levels have been shown to correlate with muscle mass and strength and be protective of sarcopenia risk. Most recent examples of relevant exercise studies are as follows: a large multicentre randomized controlled trial in HD patients (1211 recruited and 446 patients in intervention group included in analysis, and 471 controls) was performed by a German group (the DiaTT trial) investigating the effects of a 12-month intradialytic RT þ AT intervention [22]. They showed that the intervention had a significant positive effect on measures of physical function (60 s sit-to-stand test and 6 min walk test) along with some aspects of quality of life (physical health and vitality sub-scores of 36-item Short Form Health Survey) [23 && ].…”
Section: Evaluating Different Training Modalitiesmentioning
confidence: 99%